Social Networking Sites Use and English Achievement - Neman, Meily Ivane Esther; Warouw, Daniel Semuel (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Klabat, 2023)
This study was conducted due to the rise of social networking sites use among students. It aimed to find out the correlation between the use of social networking sites and students’ achievement in learning English. The participants of this study were 100 students from eleventh-grade science and social of SMA Advent Unklab. There were 19 items of questionnaire about the use of social networking sites adapted from Gupta and Bashir (2018) used as the instrument in this study. The use of social networking sites was elaborated in four factors, which are, academic factor, socialization factor, entertainment factor, and informativeness factor. This study also used English final test score to measure students’ English achievement. The data were analyzed using statistical tools, mean score for descriptive and Pearson product moment coefficient correlation to find out the correlation. The result shows that the students’ level in using social networking sites was in high level, and the factor, such as academic factor, socialization factor, entertainment factor were in high level, but informativeness factor was in moderate level. It is also found out that the students’ level in learning English was high, and the last, there is no correlation between the use of social networking sites and students’ achievement in learning English. Keywords—social networking sites, English achievement, English Penelitian ini dilakukan karena meningkatnya penggunaan situs-situs jejaring sosial oleh para siswa. Penelitian ini bertujuan untuk mencari tahu apakah ada hubungan antara penggunaan situs-situs jejaring sosial dan prestasi siswa dalam pelajaran Bahasa Inggris. Partisipan dari penelitian ini diambil dari 100 siswa kelas sebelas IPA dan Sosial SMA Advent Unklab. Instrumen dari penelitian ini adalah berupa kuesioner tentang penggunaan situs jejaring sosial yang diadaptasi dari Gupta dan Bashir (2018) yang berisi 19 butir. Penggunaan situs-situs jejaring sosial terbagi menjadi empat factor, yaitu, factor akademis, sosialisasi, hiburan, dan informasi. Selain itu, penelitian ini juga menggunakan hasil ujian akhir semester siswa untuk melihat prestasi pelajaran Bahasa Inggris. Data dari penelitian ini dianalisis menggunakan alat statistic, yaitu rerata untuk deskriptif, dan Pearson Product Moment Coefficient Correlation untuk mencari hubungan. Hasil dari penelitian ini menunjukkan bahwa tingkat penggunaan situs-situs jejaring sosial berada pada tingkat tinggi, dan faktor-faktor seperti akademik, sosialisasi, dan hiburan juga berada pada tingkat yang tinggi. Namun, faktor informasi berada pada tingkat moderat. Ditemukan juga bahwa prestasi siswa dalam pelajaran Bahasa Inggris berada pada tingkat yang tinggi, tapi tidak ada hubungan antara penggunaan situs-situs jejaring sosial dan prestasi siswa dalam pelajaran Bahasa Inggris. Kata kunci—situs jaringan sosial, prestasi belajar Bahasa Inggris, Bahasa Inggris